2017
DOI: 10.21744/irjmis.v4i5.528
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Learning Strategy, Achievement Motivation, and Communication Skill toward Learning Outcomes on the Course PMPIPS-SD at PGSD

Abstract: The Effect of Instructional Strategies, Achievement Motivation, and Communication Skills toward Learning Outcomes of PGSD on PGSD. The purpose of this research were to compare the effectiveness of the use of instructional strategies, achievement motivation, and communication skills of PGSD students in the PMPIPS-SD subject. A quasi-experimental research with pretestposttest nonequivalent control group design was carried out to achieve the goals. The data were analyzed by three-way ANOVA with SPSS 16,0 for wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Research fromHerianto (2017) shows the same results, namely students who are taught problem-based learning with high communication skills get better learning outcomes. In problem-based learning, students think more by speaking, and gain a better understanding through discussion activities, while students who are actively involved in this learning show better communication skills(Awang & Daud, 2015).…”
mentioning
confidence: 67%
“…Research fromHerianto (2017) shows the same results, namely students who are taught problem-based learning with high communication skills get better learning outcomes. In problem-based learning, students think more by speaking, and gain a better understanding through discussion activities, while students who are actively involved in this learning show better communication skills(Awang & Daud, 2015).…”
mentioning
confidence: 67%
“…The results of the study have shown that the learning tools developed have been meet the requirements of practicality. The practicality of this device is due to the fact that teachers and students easily use the tools developed because they are arranged in communicative language and are in accordance with a predetermined time allocation, so that students and teachers respond positively to the learning carried out (Herianto, 2017;Haris, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In the course of answering these questions will be understood the importance of brain functionalities in relation to learning and how it influences the teaching-learning of students. Therefore, the purpose of linking the study of the brain is to help understand the actions of the human being and his behavior in society (Arias, 2011;Herianto, 2017;Gani et al, 2018).…”
Section: Resultsmentioning
confidence: 99%